A 12-Month Follow-up, Randomized Comparison of Effectiveness and Safety of Two Hyaluronic Acid Fillers for Treatment of Severe Nasolabial Folds. Issue 3 (March 2017) - Ascher, Benjamin; Bayerl, Christiane; Kestemont, Philippe; Rzany, Berthold; Edwartz, Carolina; Podda, Maurizio
Abstract : BACKGROUND: Hyaluronic acid (HA) filler injection is an increasingly popular aesthetic procedure. OBJECTIVE: To compare the effectiveness and safety of two HA fillers (HAED and HAPER ) for the treatment of severe nasolabial folds (NLFs). MATERIALS AND METHODS: This was an evaluator-blinded and subject-blinded split-face study. At baseline, HAED or HAPER was randomly assigned to the left or right NLF. The follow-up period was 12 months. Effectiveness was assessed using the wrinkle severity rating scale (WSRS) and subject preference. Safety was assessed by adverse events and local tolerability symptoms recorded by subjects during 3 weeks after the treatment. RESULTS: At 6 months, HAED was noninferior to HAPER (assessed by mean change from baseline in WSRS score). There was a significant difference in mean WSRS score change from baseline in favor of HAED at 3 to 12 months, and a majority of subjects preferred HAED over HAPER at 12 months. However, the overall responder rate was similar between products, and it remained high throughout the study. At 12 months, approximately 80% of subjects were still responders. Both products were well tolerated and associated with a few treatment-related adverse events. CONCLUSION: To conclude, HAED was at least as effective and well tolerated for the treatment of severe NLFs as HAPER .